2002
DOI: 10.1002/jcp.10173
|View full text |Cite
|
Sign up to set email alerts
|

Retinoic acid induces expression of the interleukin‐1β gene in cultured normal human mammary epithelial cells and in human breast carcinoma lines

Abstract: Retinoic acid (RA) and its derivatives inhibit the proliferation of normal human mammary epithelial cells (HMEC) and some breast carcinoma lines by mechanisms which are not fully understood. To identify genes that mediate RA-induced cell growth arrest, an HMEC cDNA library was synthesized and subtractive screening was performed. We identified the interleukin-1beta (IL-1beta) gene as an RA induced gene in HMEC. Northern blot analyses showed that the IL-1beta gene was up-regulated as early as 2 h after RA treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 44 publications
1
13
0
Order By: Relevance
“…Tamoxifen and fenretinide combination therapy is an active treatment regimen in metastatic breast cancer patients, but not in estrogen receptor negative metastatic breast cancer or in patients whose disease had progressed after tamoxifen treatment [185]. Retinoids do not require estrogen receptors for their actions; they may affect neoplastic transformation in estrogen-negative cells, in contrast to tamoxifen, whose primary mechanism of action is through estrogen receptors [186, 187]. In spite of this, retinoids and rexinoids seem to be more active in estrogen-positive than in estrogen-negative precancerous tissue [188].…”
Section: Retinoids and Cancermentioning
confidence: 99%
“…Tamoxifen and fenretinide combination therapy is an active treatment regimen in metastatic breast cancer patients, but not in estrogen receptor negative metastatic breast cancer or in patients whose disease had progressed after tamoxifen treatment [185]. Retinoids do not require estrogen receptors for their actions; they may affect neoplastic transformation in estrogen-negative cells, in contrast to tamoxifen, whose primary mechanism of action is through estrogen receptors [186, 187]. In spite of this, retinoids and rexinoids seem to be more active in estrogen-positive than in estrogen-negative precancerous tissue [188].…”
Section: Retinoids and Cancermentioning
confidence: 99%
“…Since 231 cells do not produce IL-1b [Liu and Gudas, 2002] and IL-1b is a metastasisinducing cytokine [Hoosein, 1998] that has effects on OPG in other cell systems [Penno et al, 2002], on growth of cancer cells [Hoosein, 1998] and on metastasis to bone marrow [Hoosein, 1998], we examined the effects of IL1b on OPG production by these breast cancer cells and differences, if any, in OPG induction by IL-1b in metastasis capable and suppressed cells.…”
Section: The Bone Resorbing Cytokine Il-1b Increases Opg Expression Imentioning
confidence: 99%
“…Normal human mammary epithelial cells (HMEC) express the receptors for IL-1 family members since IL-1b inhibits significantly the proliferation of HMECs and IL-1ra blocks this growth inhibition [36]. Both expression and distribution of IL-1 family members have been well studied in human mammary cancer tissue where they regulate tumour activity within the microenvironment surrounding breast tumour [37][38][39].…”
Section: Il-1 Family and Breast Cancermentioning
confidence: 99%
“…In contrast, genes of IL-1 a , IL-1b, and IL-1ra are preferentially expressed in highly malignant and invasive mammary cell lines (BT 20, BT 549, HS 578T, and MDA-MB 231) and are not detected in other cell lines tested (MCF-7, T47-D, ZR75-1, and SKBR-3) [10]. In one study, however, the authors found no IL-1b expression in the three breast cancer cell lines MCF-7, MDA-MB231 and MDA-MB468 [36]. Collectively, this body of work suggests an autocrine/paracrine functional IL-1 system in the model of breast cancer.…”
Section: Il-1 Family and Breast Cancermentioning
confidence: 99%